'To be a slut is to be free': women in favela funk, performances of racialised femininity, and celebrity media. Issue 3 (3rd July 2022) - Moreira, Raquel
ABSTRACT: Rio de Janeiro's favela funk movement has been one of Brazil's most important contemporary cultural and musical expressions. Favela funk arose out of Rio's slums and combines diverse Brazilian and other beats from the African diaspora, and lyrics are performed with an aggressive, mocking tone, filled with sexual references. Poor women of colour in favela funk, also known as funkeiras, have been responsible for much of the celebrity media attention the movement enjoys, and with feminism's recent renewed popularity, the women have been more frequently confronted with questions of feminism, considering most of them perform songs about gendered relationships. This essay investigates how and why once some funkeiras begin to call themselves feminists, they tend to engage in a more palatable (meaning, white and middle class) version of their femininity. As their performances of femininity become more conforming, their positive visibility as feminists in celebrity media increases – a drastic change, considering that celebrity media often portrays funkeiras in demeaning and scornful ways. I conclude that celebrity culture and mainstream celebrity feminism push funkeiras into normative performances of femininity that, though not necessarily traditional, are infused with norms that privilege whiteness and middle-classness.